Blood lead level and cognitive performance in Ukrainian schoolchildren - Гнідой, І. М.; Гнiдой, Iгор Михайлович; Hnidoi, Ihor M. (My University, 2023)
Modern systematic review and meta-analysis of case-control studies demonstrate the large effect of lead exposure on IQ test scores in children under 12 years. The World Health Organization estimate that lead exposure causes 30% of the global burden of idiopathic intellectual disability. In this regard, in the most developed countries, for example, the United States, there are special government programs, International Lead Poisoning Prevention Weeks, which present an opportunity to initiate long-overdue reforms. In Ukraine, there are no state programs of such a scale as in the United States. Research on the study and limitation of the ecopathological effect of lead on the psychosomatic state of Ukrainian schoolchildren is still rare. The aim of this study was to evaluate the effect of blood lead levels on cognitive sphere indexes in urban schoolchildren resident in Odesa, Ukraine.

Сучасний систематичний огляд і мета-аналіз досліджень типу «випадок-контроль» демонструють значний негативний ефект свинцю на результати тестів IQ у дітей до 12 років. За оцінками Всесвітньої організації охорони здоров'я, вплив свинцю викликає 30% глобального тягаря ідіопатичних інтелектуальних розладів. У зв'язку з цим у найбільш розвинених країнах, наприклад, США, існують спеціальні державні програми, проводяться Міжнародні тижні профілактики отруєнь свинцем, які дають можливість ініціювати давно назрілі реформи. В Україні немає державних програм такого масштабу, як у США. Дослідження з вивчення та обмеження екопатологічного впливу свинцю на психосоматичний стан українських школярів поки що рідкісні. Метою дослідження була оцінка впливу рівня свинцю в крові на показники когнітивної сфери у школярів, які проживають у місті Одеса.
Hnidoi I. M. Blood lead level and cognitive performance in Ukrainian schoolchildren / I. M. Hnidoi // Psychosomatic Medicine and General Practice. – 2023, vol 8, № 1. – C. 1-5. DOI: 10.26766/pmgp.v8i1.376
Keywords: рівень свинцю в крові; психосоматичний стан; показники когнітивної сфери; тест на вивчення мислення; українські школяри Одеси; blood lead level; psychosomatic condition; indicators of the cognitive sphere; thinking test; Ukrainian schoolchildren of Odessa; Research Subject Categories::MEDICINE